COFFEE DIPLOMACY IN JOKOWI’S ERA: THE STRATEGY OF CULTURAL AND ECONOMIC DIPLOMACY OF INDONESIA’S FOREIGN POLICY - Anak Agung Mia Intentilia (Jurnal Ilmiah Dinamika Sosial, 2020)
Cultural and economic diplomacy are crucial and being prioritized in Indonesia's foreign policy. Coffee is one of the commodities used to promote Indonesian culture abroad while at the same time has a potential value to support the nation's economy. This article aims to describe the ways Indonesian President, Joko Widodo, conducts cultural and economic diplomacy through coffee and the involvement of state and non-state actors in Indonesia’s coffee diplomacy. This paper uses a qualitative research method. The data used are collected from the Indonesian government official websites and national media coverages during the period of Joko Widodo’s administration from 2014 to 2019. There are three main concepts used in this article, derived from the International Relations theory of diplomacy, namely: the concepts of issue areas; actors; and methods. This paper examines cultural and economic diplomacy as the issue areas, state and non-state actors as the actors, and bilateral and multilateral approaches as the methods of conducting diplomacy. The main findings of this paper are: (i) cultural and economic diplomacy through coffee diplomacy are connected to one another and conducted simultaneously; (ii) both bilateral and multilateral approaches are still relevant in conducting coffee diplomacy; (iii) both state and non-state actors are actively involved in conducting coffee diplomacy                                                                                                         Keywords: Coffee, Cultural Diplomacy, Economic Diplomacy, Jokowi, Indonesia